1998
DOI: 10.1017/s1355838298971576
|View full text |Cite
|
Sign up to set email alerts
|

Release factor RF-3 GTPase activity acts in disassembly of the ribosome termination complex

Abstract: RF3 was initially characterized as a factor that stimulates translational termination in an in vitro assay. The factor has a GTP binding site and shows sequence similarity to elongation factors EF-Tu and EF-G. Paradoxically, addition of GTP abolishes RF3 stimulation in the classical termination assay, using stop triplets.We here show GTP hydrolysis, which is only dependent on the simultaneous presence of RF3 and ribosomes. Applying a new termination assay, which uses a minimessenger RNA instead of separate tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(50 citation statements)
references
References 49 publications
1
49
0
Order By: Relevance
“…Grentzmann et al [8] have observed similar results and found that RF3 can substitute for EF-G in RRFdependent ribosome recycling reactions in vitro. One contradiction that remains to be resolved is whether RRF is able to dissociate the mRNA or not.…”
Section: Introductionmentioning
confidence: 60%
“…Grentzmann et al [8] have observed similar results and found that RF3 can substitute for EF-G in RRFdependent ribosome recycling reactions in vitro. One contradiction that remains to be resolved is whether RRF is able to dissociate the mRNA or not.…”
Section: Introductionmentioning
confidence: 60%
“…[34][35][36] In addition, RRF maintains translational accuracy during the elongation process. 37) In B. subtilis, the frr gene was expressed at a moderately high level during the early stages of sporulation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our finding that ec-RRF can work with EF-G from other species is consistent with the report that Mycobacterium tuberculosis EF-G (mt-EF-G) can complement an ec-EF-G temperature-sensitive mutant, indicating that mt-EF-G can function with ec-RRF for disassembly in vivo (Rao and Varshney 2001). This is not due to RF3 doing the role of EF-G in the RRF reaction because RF3 does not function in place of EF-G for disassembly of model post-termination complexes (data not shown) despite the fact that RF3 substituted EF-G for disassembly of complexes with artificial short nucleotides (Grentzmann et al 1998). Therefore, tt-EF-G must function with ec-RRF in vivo.…”
Section: Wwwrnajournalorgmentioning
confidence: 96%